Morphological, anatomical, palynological and karyological characters of endemic Sideritis vulcanica Hub.-Mor. (Lamiaceae) from Turkey - Erdem, Figen; Doğan, Gülden; Kıran, Yaşar; Evren, Harun (Uğur ÇAKILCIOĞLU, 2017)
Sideritis vulcanica Hub.-Mor. included in the Empedoclia section of the Lamiaceae family is an endemic species to Turkey and that is vulnerable. Sideritis vulcanica is an endemic, vulnerable and medicinal plant, therefore we focused on this species. In accordance with the new observations, additional information was added to the previous description of this species, and the description was edited. In the anatomical studies, the anatomies of the root, stem and leaf of this species have been enlightened. The shape of the pollen of S. vulcanica has been found as oblate-spheroidal. It has been determined that the polen aperture is trizonocolpate and ornamentation is reticulate. In karyological studies, chromosome counts and karyotype analyses of the species have been done and idyograms have been generated. The somatic chromosome number of S. vulcanica has been found as 2n=32 (x=16). The karyotype formula of this species consists of fourteen median chromosome and two submedian chromosome
Keywords: Pharmacology and Pharmaceutical Sciences; Eczacılık ve İlaç Bilimleri